Spain : Financial Sector Assessment Program; Technical Note; Supervision of Insurance; Alternative Models for an Independent Agency. (IMF Staff Country Reports; Country Report, 2006)
This report is the summary of a technical note on Supervision of Insurance of Spain and Alternative Models for an Independent Agency. It reviews the organizational alternatives for insurance supervision and discusses the advantages and disadvantages of alternative institutional arrangements. It presents various alternatives for an independent insurance supervisory agency for Spain.